Trends in Myopia Development Among Primary and Secondary School Students During the COVID-19 Pandemic: A Large-Scale Cross-Sectional Study - Jingfeng Mu; Jingfeng Mu; Haoxi Zhong; Haoxi Zhong; Meizhou Liu; Meizhou Liu; Mingjie Jiang; Mingjie Jiang; Xinyi Shuai; Xinyi Shuai; Yanjie Chen; Yanjie Chen; et al. (Frontiers in Public Health, 2022)
ObjectivesTo evaluate myopia development among primary and secondary school students during the coronavirus 2019 (COVID-19) pandemic.MethodsA cross-sectional study was conducted to evaluate the development of myopia among students in Shenzhen, China during the COVID-19 outbreak.ResultsThe study included 1,472,957 and 1,573,824 students in 2019 and 2020, respectively. The prevalence of myopia was 46.9 and 50.5% in 2019 and 2020, respectively. The prevalence of myopia among students in the former Shenzhen Special Economic Zone (SEZ) was higher than that in areas outside the former Shenzhen SEZ (2019: 47.0 vs. 43.7%; 2020: 50.5 vs. 47.3%). The prevalence of myopia among girls was higher than that among boys (2019: 50.4 vs. 44.0%; 2020: 54.0 vs. 47.6%). The 50th percentile (P50) of spherical equivalent refraction (SER) in the right eye among girls was lower than that in boys. The prevalence of myopia continued to increase as the grade increased, with the greatest annual increase observed in Grades 2–5 (3.4–3.9%). The P50 of SER in the right eye of students decreased as the grade increased.ConclusionsThe prevalence of myopia among students increased during the COVID-19 pandemic, especially in primary school Grades 2–5.